SISTEM KEARSIPAN DI SEKOLAH ( Studi Kasus di SMA Muhammadiyah 6 Surakarta ) - Ninghardjanti, Patni (MIIPS, 2008)
The goals of this research is to solvce the problems arouse at the archival system used by SMA Muhammadiyah 6 Surakarta. This research, qualitative approach is used in order to highlight more in a process of thing than its existence. The researchr curiously took the necessities and the priorities. Observations, depth interviews, and dokumentations are used in collecting the data related with the three major steps namely orientation, exploration, and member-check. The researcher uses some methods to measure the validity and uses double-data sources as the balancing instrument. Interactive model is appliedThe goals of this research it can be conclude: (1) The archival system is centralization system using two storage lpaces, those are in the administration room and in the head master?s room. The system of this storage is according to the latter date. (2) the archive maintenance still needs more attention, exceedingly in its security system. This condition can be seen in the laboratory. There are many useless papers lay on anywher, and never held astacking file and documen program at all. (3) The problems faced are the selecting room that is not good enough and the stacking system that is not efficient. As the result, the offices cannot do their job maximally. (4) the solutions for those problems are making the easier way to keep and save the document although it is not based on the right system.